Estimation of benzathine penicillin G demand for congenital syphilis elimination with adoption of dual HIV/syphilis rapid diagnostic tests in eleven high burden countries. - Sapan Shah; Surbhi Garg; Katherine Heath; Obiageli Ofili; Yashika Bansal; Frederic Seghers; Andrew Storey; Melanie Taylor (PLoS ONE)
Background WHO recommends use of rapid dual HIV/syphilis tests for screening pregnant women (PW) during antenatal care to prevent mother-to-child transmission. Scale-up of testing implies a need to accurately forecast and procure benzathine penicillin (BPG) to treat the additionally identified PW with syphilis. Methods Country-reported ANC coverage, PW syphilis screening and treatment coverage values in 2019 were scaled linearly to EMTCT targets by 2030 (constant increasing slope from 2019 figures to 95% in 2030) for 11 focus countries. Antenatal syphilis screening coverage was substituted with HIV screening coverage to estimate potential contribution of rapid dual HIV/syphilis tests in identifying additional PW with syphilis. BPG demand was calculated for 2019-2030 accordingly. Results The estimated demand for BPG (in 2.4 million unit vials) using current maternal syphilis prevalence and treatment coverage will increase from a baseline of 414,459 doses in 2019 to 683,067 doses (+65%) in 2021 assuming immediate replacement of single HIV test kits with rapid dual HIV/syphilis tests for these 11 countries. Continued scale up of syphilis screening and treatment coverage to reach elimination coverage of 95% will result in an estimated demand increase of 160%, (663,969 doses) from 2019 baseline for a total demand of 1,078,428 BPG doses by 2030. Conclusions Demand for BPG will increase following adoption of rapid dual HIV/syphilis test kits due to increases in maternal diagnoses of syphilis. To eliminate congenital syphilis, MNCH clinical programs will need to synergize with disease surveillance programs to accurately forecast BPG demand with scale up of antenatal syphilis screening to ensure adequate treatment is available for pregnant women diagnosed with syphilis.